Efeitos de intervenções em crianças com transtorno do espectro autista matriculadas na educação infantil - Silva, Carolina Marques (Universidade Federal de São Carlos, 2025)
Students diagnosed with Autism Spectrum Disorder may present characteristics associated with sensory and behavioral changes, and may demonstrate a greater need for support in their development. The objective of this study was to evaluate the development of children with Autism Spectrum Disorder enrolled in early childhood education, using the Operationalized Portage Inventory (OPI), to observe whether their performance is in accordance with what is expected for their age group, and to apply interventions based on performances below what is expected for their age group. Three children enrolled in the regular education system in the Early Childhood Education stage, aged between 3 and 6 years, diagnosed with Autism Spectrum Disorder (ASD) participated in the study. Data collection was carried out in three stages: application of the pre-test (OPI), interventions based on the identified needs, and application of the post-test (OPI) to assess progress. Data analysis consisted of comparing the performances obtained before and after the interventions. The results showed progress in the children's development, both in the skills directly worked on during the interventions and in other areas of development, indicating the effectiveness of the practices applied.
Effects of interventions on children with autism spectrum disorder enrolled in early childhood education
Keywords: Autismo; Desenvolvimento infantil; Inventário Portage Operacionalizado; Currículo funcional natural; Educação infantil; Autism; Child development; Operationalized Portage Inventory; Natural functional curriculum; Early childhood education; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL